Analysis of mRNA Pentatricopeptide Repeat Domain 1 as a prospective oncogene in clear cell renal cell carcinoma that accelerates tumor cells proliferation and invasion via the Akt/GSK3β/β-catenin pathway - Zhongbao Zhou; Yulong Li; Yumeng Chai; Yong Zhang; Pu Yan (Discover Oncology)
Abstract Background Although pentatricopeptide repeat domain 1 (PTCD1) has been found to modulate mitochondrial metabolic and oxidative phosphorylation, its contribution in the growth of clear cell renal cell carcinoma (ccRCC) remains unknown. Methods The Cancer Genome Atlas (TCGA) dataset was utilized to examine the transcriptional alterations, patient characteristics, clinical outcomes, as well as pathway activation of PTCD1. The Weighted Gene Co-expression Network Analysis (WGCNA) was performed to investigate potential genes that associated with PTCD1. The researchers estimated the relationship between PTCD1, tumor immunology, and epithelial mesenchymal transition (EMT). Researchers studied how PTCD1 affects the functional behavior of tumor cells in vitro. Results PTCD1 expression was greater in ccRCC samples than in normal samples, and expression increased gradually as the stage increased. In TCGA cohorts, higher PTCD1 expression was substantially associated with a poorer clinical stage, histological grading, T stage, N stage, M stage, and survival outcomes. The results of multivariate analysis showed that PTCD1 was an independent variable affecting the survival outcomes of ccRCC patients (p < 0.001). PTCD1 regulated ccRCC progression via various cancer mechanisms including PI3K-Akt signaling, focal adhesion, PD-L1 expression, and PD-1 checkpoints in cancer. WGCNA discovered a significant relationship between PTCD1 and IARS2, LRPPRC, MT-ND2, MT-CO1, MT-CO2, MT-CYB, MT-ATP6, and MT-ND4. Furthermore, PTCD1 expression levels was closely associated with immune infiltrating, immunological checkpoint, EMT, immunotherapy responsiveness, and anti-tumor medication sensitivities. Upregulation of PTCD1 in ccRCC cells resulted in considerably increased cellular invasion and migration. Mechanistically, the upregulation of PTCD1 increased the phosphorylation of AKT at Ser473 and GSK-3β at Ser9, as well as enhanced activation of Wnt/β-catenin pathway. Conclusion Elevated expression of PTCD1 was associated with malignant biological behaviors and poor outcomes of ccRCC patients, and PTCD1 may accelerate tumor cells proliferation and invasion via the Akt/GSK3β/β-catenin pathway. Our findings indicated that PTCD1 had the potential to become a new target for predicting prognosis and targeted therapy.